Informatization of educational process in high school pedagogical direction - ЕROPOVA, Еlena; MEDVEDEV, Yriy (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
Informatization is an important component of the system of higher education,which includes not only traditional methods and forms of training, but alsothe use of multimedia, telecommunications, remote sensing means of training.The use of it in teaching gives the possibility to the students carry out courseand diploma projects with the use of the programs: Word text editor, Excelspreadsheets, drawings are done in AutoCAD or ArchiCAD, graphics, PowerPoint, Corel Draw and Photoshop. Thanks to the introduction of informationtechnologies into the process of teaching students with an interest carry out thework, as it allows you to show the individual abilities and increases the cognitiveinterest in the subjects.Information technology is convenient to use when conducting ratings of thetests (with multiple choice answers, with alternative answers, with freelyконструируемыми answers), the independent work of the students. Regular useof computer programs facilitates the acquisition of in-depth and profoundknowledge, development of creative thinking and abilities, the formation of thestudents ' motivation readiness to use the acquired knowledge, abilities and skillsfor the future profession of a teacher.Future specialists of the educational sphere should own it, to solve their professionaltasks, successfully work with the children. Substantial assistance in thismay have a modern information and computer technologies, without which theteachers of today are simply not do. Ability to use in their work modern it becomesone of the main components of professional training of teachers.